Histone H3K9 butyrylation is regulated by dietary fat and stress via an Acyl-CoA dehydrogenase short chain-dependent mechanism - Zhi Yang; Minzhen He; Julianne Austin; Jessica Pfleger; Maha Abdellatif (Elsevier, 2021)
Objective: We previously reported that β-oxidation enzymes are present in the nucleus in close proximity to transcriptionally active promoters. Thus, we hypothesized that the fatty acid intermediate, butyryl-CoA, is the substrate for histone butyrylation and its abundance is regulated by acyl-CoA dehydrogenase short chain (ACADS). The objective of this study was to determine the genomic distribution of H3K9-butyryl (H3K9Bu) and its regulation by dietary fat, stress, and ACADS and its impact on gene expression. Methods and results: Using genome-wide chromatin immunoprecipitation-sequencing (ChIP-Seq), we show that H3K9Bu is abundant at all transcriptionally active promoters, where, paradoxically, it is most enriched in mice fed a fat-free vs high-fat diet. Deletion of fatty acid synthetase (FASN) abolished H3K9Bu in cells maintained in a glucose-rich but not fatty acid-rich medium, signifying that fatty acid synthesis from carbohydrates substitutes for dietary fat as a source of butyryl-CoA. A high-fat diet induced an increase in ACADS expression that accompanied the decrease in H3K9Bu. Conversely, the deletion of ACADS increased H3K9Bu in human cells and mouse hearts and reversed high-fat- and stress-induced reduction in promoter-H3K9Bu, whose abundance coincided with diminished stress-regulated gene expression as revealed by RNA sequencing. In contrast, H3K9-acetyl (H3K9Ac) abundance was minimally impacted by diet. Conclusion: Promoter H3K9 butyrylation is a major histone modification that is negatively regulated by high fat and stress in an ACADS-dependent fashion and moderates stress-regulated gene expression.